The concept of the certification system of the German Cancer Society and its impact on gynecological cancer care - Wesselmann, Simone; Beckmann, Matthias; Winter, A. (Archives of Gynecology and Obstetrics, 2014)
This article describes the status of gynecological cancer care in Germany and gives an overview of the certification of gynecological cancer care by the German Cancer Society (Deutsche Krebsgesellschaft DKG). The DKG certifies cancer centers to promote a high-quality level in the treatment of oncological patients.Searches were conducted in PubMed and ScienceDirect to identify the relevant literature. Catalog of requirements for centers certification as well as benchmark reports were used to characterize cancer care in centers certified by DKG.The certification system of the DKG has been developed to ensure comprehensive care for cancer patients in Germany. The criteria for certification are based on interdisciplinary and inter-professional care conforming to guidelines and specialist expertise. These requirements have been shown to improve structural and process quality, and thus satisfaction and health outcomes in patients.
EVALuna2:17461